2013
DOI: 10.1149/2.001312jes
|View full text |Cite
|
Sign up to set email alerts
|

Additives for Bottom-up Copper Plating from an Alkaline Complexed Electrolyte

Abstract: An alkaline, tartrate-complexed copper electrolyte containing additives that provide bottom-up fill is described. Bottom-up fill is achieved using a mixture of two additives: bis-(3-sulfopropyl) disulfide (SPS) and polyethyleneimine (PEI). Chronopotentiometric studies indicate that, unlike in conventional acidic electrolytes, SPS acts as a 'suppressor' and PEI acts as an 'anti-suppressor' in the alkaline medium. Partial-fill experiments on patterned structures confirm a SPS-PEI interaction leading to bottom-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38] Citric acid, in combination with H 2 O 2 , was once used as pretreatment solution of Cu seed layer for Ni superconformal deposition. 39 However, in this work, we have focused on citric acid as a supporting electrolyte for the replacement of sulfuric acid.…”
mentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] Citric acid, in combination with H 2 O 2 , was once used as pretreatment solution of Cu seed layer for Ni superconformal deposition. 39 However, in this work, we have focused on citric acid as a supporting electrolyte for the replacement of sulfuric acid.…”
mentioning
confidence: 99%
“…Lizama [22] also deduced that the fully deprotonated copper citrate dimer ([Cu 2 Cit 2 H -2 ] 4À ) inhibited the electro-reduction of copper ion by the electrochemical study combined with the chemical equilibrium diagram. Joi and Im et al [23][24][25] reported the application of citrate-coordinated copper electroplating bath on the dual-damascene copper metallization. After improving the alkaline citrate copper plating process by decreasing the solution viscosity and increasing the deposition current density, we [26,27] successfully applied the process in the through-hole metallization of PCB and MEMS (Micro-electromechanical Systems) manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical measurements and trench filling results are presented for the tartrate complexed cupric sulfate electrolyte, containing 0.1 mol/L CuSO 4 · 2H 2 O + 0.5 mol/L Na 2 C 4 H 4 O 6 · 2H 2 O. The electrolyte differs from that in the earlier study 54 in the cation of the tartrate (KNaC 4 H 4 O 6 · 2H 2 O) and 1800 MW branched PEI (Alfa-Aesar a ) rather than 600 MW. As in the earlier study, the pH was adjusted to 12.5 through the addition of sodium hydroxide.…”
mentioning
confidence: 96%
“…53 A more recent publication details superconformal deposition in micrometer size trenches in a tartrate complexed Cu electrolyte of pH > 12. 54 Superconformal filling was obtained in the presence of two additives, polyethyleneimine (PEI) and bis-(3-sulfopropyl) disulfide (SPS), with conformal filling obtained in the presence of just one additive. The superconformal filling was suggested to be consistent with the Curvature Enhanced Accelerator Coverage (CEAC) mechanism, the SPS referred to as a "suppressor" and the PEI referred to as an "antisuppressor".…”
mentioning
confidence: 99%